Impact of the Drg System on Technical Efficiency: A Case Study of Chilean High-Complexity Hospitals - Villalobos-Cid, M (IEEE Computer Society, 2024)
The efficient use of resources is critical in healthcare. Despite significant expenditure increases, hospital productivity has stayed the same proportionally in Chile, suggesting potential issues in resource management. Technical efficiency (TE) allows the comparison of hospitals with similar profiles of patients or case-mix, which is critical for understanding how resources are utilised to generate healthcare outputs. Internationally, the Diagnosis Related Groups (DRG) system has been widely used as a standard to normalise and perform fair comparisons of healthcare production. However, in Chile, its implementation could be improved. The present study evaluates the TE of high-complexity public hospitals in Chile using computational methods, including Data Envelopment Analysis (DEA) and the Malmquist productivity index (MPI). We compare the impact of the DRG system in TE estimation with other categorisations used in the related literature, such as the Chilean Ministry of Health and geographical categorisation. Results reveal significant differences between the TE estimated (5% to 50%), discrepancies in rankings, and resource utilisation. These findings suggest that the full use of the DRG system in TE must be included since it enhances resource allocation and management in public hospitals. © 2024 IEEE.